Qur'anic Terminology on Human Sense, Rational and Intuitive Potency - Jamal, Khairunnas; Sawaluddin, Sawaluddin (AL-FIKRA, 2021)
This study aims to analyze the terminology of the Qur'an about human potential. This research is designed in the form of library research or library research that uses various library sources as a source of research data. The data studied were sourced from the Qur'an, books and research results of Muslim scholars and scholars. The data used is divided into two, primary and secondary data. Primary data includes the Qur'an which talks about the terminology of the Qur'an about human potential. Secondary data to support primary data, taken from books and relevant research results related to the focus of the study. The data analyst used the text analysis method, namely selecting key terms from the vocabulary of the Qur'an, determining the basic meaning and relational meaning and concluding and integrating these concepts into a one general concept. The results of this study are: First; The potential of Indra, mentioned in the Qur'an with three terms al-sam'u repeated 185 times, al-bashr repeated 139 times, and al-dhuq, repeated 48 times. Second, the potential of reason, etymologically, the term "aql" is mentioned in the Qur'an more than 49 words, which are collected in (dzakara), (faqiha), ('alima), (tadab bara), (tafakkur) and Ulu al -chapter. Third, the potential of the heart, the mashdar form of the root qalaba-yaqlibu-kalbuan which means turning or turning. The Qur'an uses the term heart to refer to the human heart, but the heart or heart In the Qur'an the word heart is mentioned 122 times spread over 45 letters and 112 verses, collected in the terms qalb, shadr, lubb, and fu'Äd.